Parthenium hysterophorus: Novel adsorbent for the removal of heavy metals and dyes - S.A. Bapat; D.K. Jaspal (Global Journal of Environmental Science and Management)
Heavy metals and dyes are major contributors in contamination of water streams. These contaminants enter into our eco- system, thus posing a significant threat to public health, ecological equilibrium and environment. Thus a combined discharge of these contaminants results in water pollution with high chemical oxygen demand, biological oxygen demand, color, particulate matter, suspended particles and odor. The mounting pollution of the water bodies has attracted attention of the researchers towards the development of novel techniques and materials for water pollution. The paper describes the use of such a material Parthenium hysterophorus, a weed, explored for water purification. The potential of the weed has been tested for several heavy metals and dyes as described in this paper. As per literature the weed is capable of showing adsorption tendency up to 90% in certain cases for some heavy metals and dyes. Powdered weed, activated carbon, ash etc. of Parthenium have been employed for the removal process.